Projections of the insular cortex to orbitofrontal and medial prefrontal cortex: A tracing study in the rat - Mathiasen, Mathias L.; Aggleton, John P.; Witter, Menno P. (Frontiers in Neuroanatomy, 2023)
The dense fiber pathways that connect the insular cortex with frontal cortices are thought to provide these frontal areas with interoceptive information, crucial for their involvement in executive functions. Using anterograde neuroanatomical tracing, we mapped the detailed organization of the projections from the rat insular cortex to its targets in orbitofrontal (OFC) and medial prefrontal (mPFC) cortex. In OFC, main insular projections distribute to lateral and medial parts, avoiding ventral parts. Whereas projections from the primary gustatory cortex densely innervate dorsolateral OFC, likely corresponding to what in primates is known as the secondary gustatory cortex, these projections avoid mPFC. Instead, mPFC is targeted almost exclusively by projections from agranular fields of the insular cortex. Finally, “parietal” domains of the insular cortex project specifically to the dorsolateral OFC, and strongly innervate ventral portions of mPFC, i.e., the dorsal peduncular cortex.